2015
DOI: 10.1016/j.apjtm.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of PEDF promoting the proliferation of lens epithelial cells in human eyes

Abstract: In human eyes, PEDF may function as cytotropic factor to promote survival of LECs through anti-apoptosis and reducing-expression of VEGF. Decrease of PEDF content in LECs probably modulates the pathophysiological process of lens cells and further cataractogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In the human eye, it is thought that PEDF can act as a cytotropic factor to ensure the survival of lens epithelial cells due to its anti‐apoptosis characteristics. The reduction of PEDF content in lens epithelial cells may modulate the pathophysiologic process and cataract pathogenesis of lens cells …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the human eye, it is thought that PEDF can act as a cytotropic factor to ensure the survival of lens epithelial cells due to its anti‐apoptosis characteristics. The reduction of PEDF content in lens epithelial cells may modulate the pathophysiologic process and cataract pathogenesis of lens cells …”
Section: Discussionmentioning
confidence: 99%
“…Synthesis and secretion of PEDF has been shown to significantly decrease in aged cells in studies of epithelial cell cultures . PEDF is thought to be involved in the pathogenesis and development of some age‐related diseases . Liu et al demonstrated that PEDF levels decrease with age and the decrease shows a significant correlation with age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations